Ecofriendly spectrophotometric methods for simultaneous determination of remdesivir and moxifloxacin hydrochloride as co administered drugs in corona virus treatment - Eman A. Madbouly; Abdalla A. El-Shanawani; Sobhy M. El-adl; Ahmed S. Abdelkhalek (Scientific Reports)
Abstract Remdesivir and moxifloxacin hydrochloride are among the most frequently co-administered drugs used for COVID-19 treatment. The current work aims to evaluate green spectrophotometric methodologies for estimating remdesivir and moxifloxacin hydrochloride in different matrices for the first time. The proposed approaches were absorbance subtraction, extended ratio subtraction and amplitude modulation methods. In order to determine the absorbance of the investigated medications in combination at the isoabsorptive point, the pure moxifloxacin hydrochloride absorbance factor is applied using the absorbance subtraction method, which modifies the zero absorption spectra of the drugs under investigation at the isoabsorptive point (229 nm). The spectrum of moxifloxacin hydrochloride is more extended in the plateau area between 340 and 400 nm, where remdesivir exhibits no absorption. So, also, the ratio spectra were successfully manipulated for quantification of the two drugs. Regarding the pharmacokinetic profile of remdesivir (Cmax 4420 ng/mL) and moxifloxacin hydrochloride (Cmax 3.56 µg/mL), the proposed methods were effectively used to spectrophotometrically determine remdesivir and moxifloxacin hydrochloride in plasma matrix. The new approach was validated using the ICH guidelines for specificity, linearity, precision, and accuracy. The greenness of the reported methodologies was evaluated using two metrics: the analytical eco-scale and the green analytical procedure index.